2014
DOI: 10.3109/07434618.2014.904923
|View full text |Cite
|
Sign up to set email alerts
|

Eye Tracking as a Measure of Receptive Vocabulary in Children with Autism Spectrum Disorders

Abstract: This study examined the utility of eye tracking research technology to measure speech comprehension in 14 young boys with autism spectrum disorders (ASD) and 15 developmentally matched boys with typical development. Using eye tracking research technology, children were tested on individualized sets of known and unknown words, identified based on their performance on the Peabody Picture Vocabulary Test. Children in both groups spent a significantly longer amount of time looking at the target picture when previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 56 publications
(70 reference statements)
1
52
0
1
Order By: Relevance
“…Because eye-gaze methods require only passive engagement-namely, sitting and looking at a screen-they have limited behavioral demands relative to assessment techniques that require a purposeful response (Abbeduto, Kover, & McDuffie, 2012;Falck-Ytter, Bölte, & Gredebäck, 2013;Karatekin, 2007). This means that eyegaze methods may be well suited for children with NDD who are unable to follow an examiner's overt requests or are distressed by them (Brady, Anderson, Hahn, Obermeier, & Kapa, 2014;Charman, Drew, Baird, & Baird, 2003). Factors such as social engagement or motor planning can affect the content validity of some examiner-directed tasks, but, depending on the experimental design, eye-gaze methods may lessen these effects and/or quantify their impact on processing and learning.…”
Section: Limited Behavioral Response Demandsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because eye-gaze methods require only passive engagement-namely, sitting and looking at a screen-they have limited behavioral demands relative to assessment techniques that require a purposeful response (Abbeduto, Kover, & McDuffie, 2012;Falck-Ytter, Bölte, & Gredebäck, 2013;Karatekin, 2007). This means that eyegaze methods may be well suited for children with NDD who are unable to follow an examiner's overt requests or are distressed by them (Brady, Anderson, Hahn, Obermeier, & Kapa, 2014;Charman, Drew, Baird, & Baird, 2003). Factors such as social engagement or motor planning can affect the content validity of some examiner-directed tasks, but, depending on the experimental design, eye-gaze methods may lessen these effects and/or quantify their impact on processing and learning.…”
Section: Limited Behavioral Response Demandsmentioning
confidence: 99%
“…Having infants and toddlers sit on the lap of a parent or caregiver often places children at an appropriate height to view the screen, and the presence of a familiar adult provides reassurance. Other studies use booster seats with straps to minimize movement and adapt for differences in body size (e.g., Brady et al, 2014). Because automatic eye trackers require participants to be seated within a relatively restricted three-dimensional space, it is important to allow adjustment for participants of variable heights (Sasson & Elison, 2012).…”
Section: Scaffolding the Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…We track their gaze during this task to determine where they focus when they make their decision. Previous uses of eye-tracking technology have suggested that children's attention to stimuli may indicate an implicit understanding (e.g., [45,46]). In addition to the general effect of focus on phonology on orthographic knowledge we expect different levels of response for different orthographic combinations.…”
Section: Child Development Researchmentioning
confidence: 99%